If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 = 3(3x + 1) Reorder the terms: -15 = 3(1 + 3x) -15 = (1 * 3 + 3x * 3) -15 = (3 + 9x) Solving -15 = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -15 + -9x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 -15 + -9x = 3 + 0 -15 + -9x = 3 Add '15' to each side of the equation. -15 + 15 + -9x = 3 + 15 Combine like terms: -15 + 15 = 0 0 + -9x = 3 + 15 -9x = 3 + 15 Combine like terms: 3 + 15 = 18 -9x = 18 Divide each side by '-9'. x = -2 Simplifying x = -2
| 4(y+6)=5(y-8) | | 3(13+2d)-7=13-(12+2d) | | -21=7(y+2) | | 3-4q=10+10q | | X-3+14=5 | | -3.1x=7.75 | | 4z+17=3z+6 | | 8(w-3)=40 | | 8x-(4x+9)= | | 4-5x=-6 | | 4y+4=3y-9 | | (15+x)+(17+x)=72 | | -6a+3=-3(2a-q) | | -32+8+(-22)=-12 | | 7x+4x=68 | | -9y-12=5y+16 | | 2x(54)=7 | | 5(3f+21)=15f+105 | | -9x-4=-10-8x | | 124=6x+7x-6 | | 4x+12=-5x+51 | | 0.45(20)+0.8x=0.7(20+x) | | (x-8)(x^2+4x-12)=0 | | 2x-2(6x-8)=24 | | 1.75x+50=2.50x+39.99 | | 10=-8x+42 | | -8x+22=22 | | 8z-11=1 | | -2x-2-7x=-92 | | 3.3=c/3 | | 8x-7x=-2 | | 15m+23m= |